Electro-Optical Sampling of Single-Cycle THz Fields with Single-Photon Detectors - Taylor Shields; Adetunmise C. Dada; Lennart Hirsch; Seungjin Yoon; Jonathan M. R. Weaver; Daniele Faccio; Lucia Caspani; Marco Peccianti; Matteo Clerici (Sensors, 2022)
Electro-optical sampling of Terahertz fields with ultrashort pulsed probes is a well-established approach for directly measuring the electric field of THz radiation. This technique usually relies on balanced detection to record the optical phase shift brought by THz-induced birefringence. The sensitivity of electro-optical sampling is, therefore, limited by the shot noise of the probe pulse, and improvements could be achieved using quantum metrology approaches using, e.g., NOON states for Heisenberg-limited phase estimation. We report on our experiments on THz electro-optical sampling using single-photon detectors and a weak squeezed vacuum field as the optical probe. Our approach achieves field sensitivity limited by the probe state statistical properties using phase-locked single-photon detectors and paves the way for further studies targeting quantum-enhanced THz sensing.